El queratocono en pacientes de una institución privada de la ciudad de Quito, Ecuador en el período de Enero de 2015 a octubre de 2016 - Mansfield Rojas, Nicole (2017)
Keratoconus is a non-inflammatory ectasia of the cornea, of unknown etiology, characterized by cone deformation and progressive thinning of the cornea. There are many theories as to its cause, within which is the presence of ocular allergy and constant eye rubbing. These changes lead to alterations in vision. Both clinical findings and findings in slit lamp, retinoscopy, keratometry and topography are required for diagnosis. Taking the rotating camera Scheimpflug as the most complete tool to assess patients. Background. Keratoconus has a prevalence of 54.5 per 100,000 people, but this has been seen to vary by geographic location. There has been a strong relationship between keratoconus and allergic conjunctivitis due to the constant rubbing of the eyes. Allergic conjunctivitis affects 25% of the population of world and one study reported that 36% of patients with keratoconus had allergic disease. Justification. Keratoconus is a pathology that produces significant distortions in vision and therefore influences the socio-affective and cultural life of patients suffering from it. There are no local data on the presence of the disease, nor are there studies that indicate the population characteristics of the people who suffer from it in this country. This approach seeks to encourage future systematic studies of this disease. Objective. The objective of this study is to describe the population diagnosed with keratoconus in a private ophthalmologic clinic in Quito between January 2015 and October 2016. Methodology. A retrospective descriptive study was carried out based on clinical histories and recording with Scheimpflug rotary camera. Results: In the period